Morphology and phenotype characteristics of atherosclerotic plaque in patients with acute coronary syndrome: contemporary optical coherence tomography findings. Issue 8 (12th February 2021) - Gomes, Paula Mendonça; Almeida, Breno Oliveira; Marinelli Pedrini, Stella; Freitas, Bárbara Palma; Júnior, José Mariani; Lemos, Pedro A.; Fonseca, Francisco H.; Mintz, Gary S.; Caixeta, Adriano
Abstract : Background: Contemporary optical coherence tomography (OCT) findings in patients with acute coronary syndromes (ACS) are still subject of controversy. We sought to use OCT to evaluate plaque morphology and phenotype classification in patients with ACS. Methods: Using optical coherence tomography, culprit lesions were morphologically classified as plaque rupture, plaque erosion, calcified nodule, thin-cap fibroatheroma, thick-cap fibroatheroma (TCFA) or fibrotic, fibrocalcific or fibrolipidic plaque. Quantitative and qualitative analyses also included cholesterol crystals, neovascularization, spotty calcification and thrombus. Results: Of the 110 lesions imaged from June 2012 to April 2016, 54 (49%) were in patients with unstable angina (UA), 31 (28%) were in non-ST-elevation myocardial infarction (STEMI) patients and 25 (23%) were in STEMI patients. Compared with STEMI patients, patients with UA/non-STEMI were older and had more hypertension, hypercholesterolemia, known coronary artery disease, prior myocardial infarction and higher use of antiplatelet therapy. More patients with STEMI had lipidic arc >90% (36.6 versus 70.8%, P = 0.003), red and mixed thrombus (12.9 versus 28.0% and 7.1 versus 44.0%, respectively, all P < 0.001), plaque rupture (29.4 versus 76.0%, P < 0.001) and TCFA (57.1 versus 84.0%; P = 0.01). Predictors of plaque rupture were STEMI at presentation (odds ratio: 9.35, 95% confidence interval: 1.66–52.61, P = 0.01) and diabetes mellitus (odds ratio: 6.16, 95% confidence interval: 1.33–28.58, P = 0.02). Conclusions: In this single-center study, the culprit lesion of patients with STEMI had more lipid, red and mixed thrombus, plaque rupture and TCFA versus patients with UA/non-STEMI. Clinical presentation may be driven by distinct pathophysiologic mechanisms in patients with ACS.